Franz Mayer of Munich : Mayer'sche Hofkunstanstalt : architecture, glass, art - Mayer, Gabriel, 1938-; Clarke, Brian, 1953-; Harrison, Martin, 1945-; Knapp, Gottfried; Mayer'sche Hofkunstanstalt GmbH. (München : Hirmer, 2012)
Founded in 1847, Franz Mayer of Munich is one of the worlds foremost studios for mosaics and stained glass. Dedicated to the restoration of historic works as well as the execution of contemporary projects for artists and architects worldwide, the family-owned company is widely lauded for its commitment to maintaining the highest standards of quality. Generously illustrated, Franz Mayer of Munich takes readers on a tour of the company's long history, from its genesis as a fine arts manufacturer to the establishment of a stained glass department in 1860 and the period of rapid growth and expansion including the opening of branches in London and New York that followed. In 1925, a mosaic department was added and the company began honing its expertise in these areas, enabling ever more ambitious rebuilds and restorations. In addition to the company's history, essays and photographs provide insight into Franz Mayer of Munich today, documenting projects' development and realization. Works by Franz Mayer of Munich can be seen in public spaces all across the world, but there have been few accessible books about the company. This book fills that gap and will be welcomed by those interested in learning more.
boek
Keywords: Glass painting and staining -- Germany